Production method of ceramic continuous fiber having carbon layer

JP2025025893APending Publication Date: 2025-02-21TOSOH CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023131111
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-10
Publication Date
2025-02-21

AI Technical Summary

Benefits of technology

【0010】 本開示により、サイジング材を有さない又は一定以上の大きさを有するセラミックス連続繊維への適用が可能であり、なおかつ、炭素の被覆厚の制御が容易な、炭素被覆セラミックス連続繊維の製造方法、セラミックス連続繊維への炭素被覆方法、及び、これより得られる炭素被覆セラミックス連続繊維を含むセラミックスマトリックス複合材料の少なくともいずれかを提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025025893000001
    Figure 2025025893000001
  • Figure 2025025893000002
    Figure 2025025893000002
  • Figure 2025025893000003
    Figure 2025025893000003
Patent Text Reader

Abstract

To provide at least one of a production method of a carbon-coated ceramic continuous fiber, applicable to a ceramic continuous fiber not having a sizing material or having a fixed size or more, and easily controlling a coating thickness of carbon, a carbon coating method on a ceramic continuous fiber, and a ceramic matrix composite material including the carbon-coated ceramic continuous fiber obtained by the method.SOLUTION: A production method of a carbon-coated ceramic continuous fiber includes the steps of: an impregnation step of impregnating a carbon precursor-containing solution into a ceramic continuous fiber; a washing step of washing the ceramic continuous fiber including the carbon precursor; and a heat treatment step of heat-treating a precursor continuous fiber before washing in an inert atmosphere or a vacuum atmosphere.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a method for making continuous ceramic fibers having a carbon layer. [Background technology]

[0002] In ceramic matrix composite materials consisting of continuous ceramic fibers and a ceramic matrix, studies are being conducted to coat the surfaces of the continuous ceramic fibers with carbon to suppress adhesion to the ceramic matrix, thereby improving scratch resistance and heat resistance.

[0003] For example, Non-Patent Document 1 discloses alumina-mullite mixed continuous fibers coated with carbon by a CVD method. Non-Patent Document 2 reports that a ceramic continuous fiber can be coated with carbon to a thickness of 2 nm by immersing the fiber in a methanol solution of polyvinyl acetate, drying and heat treating it, and that a carbon coating to a thickness of 10 nm can be achieved by repeating this process five times. Furthermore, Patent Document 1 discloses that a resin used as a sizing material for ceramic continuous fibers is heat treated to form a carbon nanotube coating layer. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Special Publication No. 2012-536852 [Non-patent literature]

[0005] [Non-Patent Document 1] J.Am.Ceram.Soc.,83[2],(2000)329-336. [Non-Patent Document 2] J.Am.Ceram.Soc.,91

[12] ,(2008)4003-4008. Summary of the Invention [Problem to be solved by the invention]

[0006] The CVD method has a limited range of carbon coating, and when applied to coating ceramic continuous fibers having a certain size or larger, the carbon layer obtained becomes non-uniform. In addition, in the method of Non-Patent Document 2, the impregnation and heat treatment steps had to be repeated five times to obtain a carbon coating with a thickness of 10 nm. Furthermore, since Patent Document 1 uses a sizing material as a carbon precursor, it could not be applied to ceramic continuous fibers that do not contain a sizing material.

[0007] In view of these problems, the present disclosure aims to provide at least one of a method for producing a carbon-coated ceramic continuous fiber, a method for coating a ceramic continuous fiber with carbon, and a ceramic matrix composite material containing the carbon-coated ceramic continuous fiber obtained thereby, which can be applied to ceramic continuous fibers that do not have a sizing material or that have a certain size or larger, and which allows easy control of the carbon coating thickness. [Means for solving the problem]

[0008] In this disclosure, we have investigated carbon coating of continuous ceramic fibers. As a result, we have found that in a coating method by impregnation with a polymer solution, a carbon coating of any thickness can be formed on continuous ceramic fibers by performing a simple post-treatment without the need for repeated operations.

[0009] That is, the present invention is as defined in the claims, and the gist of the present disclosure is as follows. [1] A method for producing a carbon-coated ceramic continuous fiber, comprising: an impregnation step of impregnating a ceramic continuous fiber with a solution containing a carbon precursor; a washing step of washing the ceramic continuous fiber containing the carbon precursor; and a heat treatment step of heat treating the washed precursor continuous fiber in an inert atmosphere or a vacuum atmosphere. [2] The method according to the above [1], wherein the washing is performed using a washing liquid. [3] The method according to [2] above, wherein the cleaning liquid is at least one selected from the group consisting of water, methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, butyl alcohol, isobutyl alcohol, acetone, methyl ethyl ketone, methyl isobutyl ketone, diisobutyl ketone, cyclohexanone, diacetone alcohol, benzene, toluene, xylene, ethyl acetate, methyl acetate, butyl acetate, methoxybutyl acetate, isobutyl acetate, normal hexane, heptane, cyclohexane, methylcyclohexane, ethylene glycol, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, N,N-dimethylformamide, tetrahydrofuran, N-methyl-2-pyrrolidone, and 1,4-dioxane. [4] The method according to any one of the above [1] to [3], wherein the ceramic continuous fiber is a ceramic continuous fiber cloth. [5] The method according to any one of the above [1] to [4], wherein the ceramic continuous fibers are one or more continuous fibers selected from the group consisting of silicon carbide, alumina, and mullite. [6] The method according to any one of [1] to [5] above, wherein the carbon precursor is one or more selected from the group consisting of polyvinyl chloride, polyvinyl alcohol, polyvinyl acetate, polycarbonate, polyvinyl butyral, polystyrene, acrylic resin, methacrylic resin, polyphenylene oxide, thermoplastic polyurethane, polyethylene, polypropylene, polyamide, polyacetal, polyphenylene sulfide, vinylidene chloride resin, polyethylene terephthalate, phenolic resin, urea resin, melamine resin, unsaturated polyester resin, diallyl phthalate resin, epoxy resin, polyimide, polyamino bismaleimide, and thermosetting polyurethane. [7] A method for producing a ceramic matrix composite material, comprising using the carbon-coated ceramic continuous fiber obtained by the method according to any one of [1] to [6] above. Effect of the Invention

[0010] The present disclosure can provide at least one of a method for producing a carbon-coated ceramic continuous fiber, a method for coating a ceramic continuous fiber with carbon, and a ceramic matrix composite material containing the carbon-coated ceramic continuous fiber obtained thereby, which can be applied to ceramic continuous fibers that do not have a sizing material or that have a certain size or larger, and in which the carbon coating thickness can be easily controlled. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, the present disclosure will be described in detail by showing an example of an embodiment, but the present disclosure is not limited to the following embodiment.

[0012] "Continuous fiber" refers to a long fiber in the form of a thread, and further to a long fiber in the form of a thread that can be woven by a spinning machine, and particularly refers to a fiber other than a short fiber. "Ceramic fiber" refers to a polycrystalline ceramic that has been spun, and further to a polycrystalline ceramic in the form of a thread. Furthermore, ceramic fibers can be classified into "ceramic short fiber" and "ceramic continuous fiber" based on their fiber length. Ceramic short fiber refers to a ceramic fiber with a fiber length of less than 500 μm. On the other hand, "ceramic continuous fiber" refers to a continuous fiber made of ceramics, and particularly refers to a ceramic fiber other than a short ceramic fiber (ceramic fiber with a fiber length of 500 μm or more). Furthermore, ceramic fiber may be an independent fiber, or may be a fiber in which two or more fibers are assembled (hereinafter also referred to as a "fiber bundle"). [Manufacturing method of carbon-coated ceramic continuous fibers] This embodiment is a method for producing a carbon-coated ceramic continuous fiber, which includes an impregnation step of impregnating a ceramic continuous fiber with a solution containing a carbon precursor, a washing step of washing the ceramic continuous fiber containing the carbon precursor, and a heat treatment step of heat treating the washed precursor continuous fiber in an inert atmosphere or a vacuum atmosphere. This makes it possible to obtain a ceramic continuous fiber having a carbon layer of a desired thickness, i.e., a carbon-coated ceramic continuous fiber, without repeating the impregnation step, washing step, and heat treatment step multiple times.

[0013] The ceramic continuous fiber to be subjected to the impregnation step is preferably a ceramic continuous fiber cloth. The type of ceramic continuous fiber may be any type of ceramic continuous fiber that can be used as a reinforcing material for ceramic matrix composites (hereinafter also referred to as "CMC"), and is preferably an oxide ceramic continuous fiber, more preferably one or more continuous fibers selected from the group consisting of silicon carbide, alumina, and mullite, and particularly preferably a mixed fiber of alumina and mullite.

[0014] The ceramic continuous fibers preferably do not contain a sizing material, but may contain a sizing material such as one or more selected from the group consisting of polyvinyl alcohol, polyurethane resin, epoxy resin, polybutadiene, polyalkylene glycol, polyolefin resin, vinyl ester resin, saturated polyester resin, unsaturated polyester resin, polyamide resin, polyimide resin, polyamideimide resin, acrylic resin, polypropylene resin, and pitch-based resin.

[0015] The carbon precursor to be subjected to the impregnation step may be any compound that is carbonized by the heat treatment step, and may be, for example, one or more selected from the group consisting of polyvinyl chloride, polyvinyl alcohol, polyvinyl acetate, polycarbonate, polyvinyl butyral, polystyrene, acrylic resin, methacrylic resin, polyphenylene oxide, thermoplastic polyurethane, polyethylene, polypropylene, polyamide, polyacetal, polyphenylene sulfide, vinylidene chloride resin, polyethylene terephthalate, phenolic resin, urea resin, melamine resin, unsaturated polyester resin, diallyl phthalate resin, epoxy resin, polyimide, polyamino bismaleimide, and thermosetting polyurethane, and at least one of polyvinyl acetate and phenolic resin is preferred. In addition, when a thick carbon coating is formed, it is more preferable that the carbon precursor is a phenolic resin, and when a thin and uniform carbon coating is formed, it is preferable that the carbon precursor is polyvinyl acetate.

[0016] The solvent in the solution containing the carbon precursor (hereinafter also referred to as "precursor solution") may be any solvent in which the carbon precursor dissolves, and is preferably an alcohol solution, or more preferably a methanol solution.

[0017] The content of the carbon precursor contained in the precursor solution is arbitrary, and the higher the content of the carbon precursor, the thicker the carbon coating obtained tends to be. The content of the carbon precursor in the precursor solution is, as the mass ratio of the carbon precursor to the mass of the precursor solution, 0.1 mass% or more, 0.5 mass% or more, or 1 mass% or more, and may be 30 mass% or less, 25 mass% or less, or 20 mass% or less, and is preferably 0.1 mass% or more and 30 mass% or less, 0.5 mass% or more and 25 mass% or less, or 1 mass% or more and 20 mass% or less. For example, when the carbon precursor is polyvinyl acetate, the content of the carbon precursor (polyvinyl acetate content) may be 0.5 mass% or more and 25 mass% or less, or 1 mass% or more and 20 mass% or less, and when the carbon precursor is a phenolic resin, the content of the carbon precursor (phenolic resin content) may be 0.5 mass% or more and 10 mass% or less, or 1 mass% or more and 10 mass% or less.

[0018] In the impregnation step, the ceramic continuous fiber is impregnated with the precursor solution. As a result, the ceramic continuous fiber contains a carbon precursor. The carbon precursor is particularly contained on the surface of the ceramic continuous fiber. The ceramic continuous fiber can be impregnated with the precursor solution in any manner that allows the ceramic continuous fiber to be impregnated with the precursor solution, and the ceramic continuous fiber can be immersed in the precursor solution.

[0019] The impregnation temperature may be from 10° C. to 40° C., or even room temperature (25±5° C.). The impregnation time may be appropriately adjusted depending on the amount of the precursor solution to be subjected to the impregnation step, the size of the ceramic continuous fiber, and the like, and may be, for example, from 30 minutes to 24 hours.

[0020] In the washing step, the ceramic continuous fiber containing a carbon precursor (hereinafter also referred to as "precursor-containing fiber") is washed. After the impregnation step, the precursor solution remaining in the precursor-containing fiber is removed, which can suppress the redissolution of the carbon precursor in the solvent from the impregnation step to the heat treatment step, and it is believed that the carbon precursor contained in the ceramic continuous fiber can be carbonized without being damaged. In addition, since the precursor present in the gaps formed between the continuous fibers is removed by washing, when the ceramic matrix is ​​combined with the ceramic matrix, the ceramic matrix is ​​more likely to impregnate the internal gaps formed between the continuous fibers.

[0021] The washing may be performed by any method capable of removing excess precursor solution. This allows the excess precursor solution to be efficiently removed while leaving the necessary carbon precursor on the continuous fiber surface. As a result, a thicker carbon layer is more easily formed than in the past. The washing liquid may be, for example, at least one selected from the group consisting of water, methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, butyl alcohol, isobutyl alcohol, acetone, methyl ethyl ketone, methyl isobutyl ketone, diisobutyl ketone, cyclohexanone, diacetone alcohol, benzene, toluene, xylene, ethyl acetate, methyl acetate, butyl acetate, methoxybutyl acetate, isobutyl acetate, normal hexane, heptane, cyclohexane, methylcyclohexane, ethylene glycol, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, N,N-dimethylformamide, tetrahydrofuran, N-methyl-2-pyrrolidone, and 1,4-dioxane, and is preferably at least one of water and ethanol.

[0022] The washing step is preferably carried out using a washing liquid in which the carbon precursor has a lower solubility than the solvent of the precursor solution. For example, when a precursor solution whose solvent is methanol is used, the washing liquid is ethanol.

[0023] The manufacturing method of this embodiment may, if necessary, include a drying step of drying the washed ceramic continuous fiber containing the carbon precursor prior to the heat treatment step, which suppresses re-dissolution of the carbon precursor in the washing liquid in the heat treatment step, and as a result, the obtained carbon coating tends to be more homogeneous.

[0024] The drying conditions may be any conditions that can remove the solvent, and the following conditions can be exemplified. Dry atmosphere: Oxidizing or inert atmosphere, or even air Drying temperature: 50℃ to 120℃, or 55℃ to 110℃

[0025] The drying time may be adjusted appropriately depending on the size of the ceramic continuous fibers and the drying method used, and may be, for example, from 10 minutes to 48 hours, or from 30 minutes to 24 hours.

[0026] In the heat treatment step, the washed precursor continuous fiber is heat treated in an inert atmosphere or vacuum atmosphere. This carbonizes the carbon precursor contained in the ceramic continuous fiber, and a carbon-coated ceramic continuous fiber is obtained. If the heat treatment is performed in another atmosphere, such as an oxygen atmosphere, the carbon precursor is burned away and a uniform carbon layer cannot be obtained.

[0027] The heat treatment may be performed in an inert atmosphere or a vacuum atmosphere. The inert atmosphere may be one or more atmospheres selected from the group consisting of helium, neon, argon, krypton, xenon, radon, nitrogen, and carbon dioxide, preferably a nitrogen atmosphere or an argon atmosphere, and more preferably a nitrogen atmosphere. The vacuum atmosphere is preferably a vacuum atmosphere of 0.1 MPa or less.

[0028] The heat treatment temperature may be any temperature at which the carbonization of the carbon precursor proceeds, and may be appropriately adjusted depending on the heat treatment atmosphere. The heat treatment temperature is preferably a temperature at which a carbon layer is easily formed on the surface of the ceramic continuous fiber without excessively heating the fiber. Examples of such a temperature include 300°C or more or 400°C or more, and 1500°C or less, 1000°C or less, or 530°C or less, and 300°C or more and 1500°C or less, or 400°C or more and 530°C or less are preferred.

[0029] The heat treatment time may be adjusted as appropriate depending on the heat treatment temperature, heat treatment atmosphere, and the performance of the heat treatment furnace, and may be, for example, from 10 minutes to 72 hours, from 20 minutes to 48 hours, or from 30 minutes to 24 hours.

[0030] A carbon-coated ceramic continuous fiber having a desired thickness is obtained through an impregnation step, a washing step, a drying step as required, and a heat treatment step (hereinafter, these steps are collectively referred to as a "coating step"). Therefore, in the manufacturing method of this embodiment, the coating step may be performed only once, but the coating step may be repeated multiple times (for example, from 2 to 5 times) depending on the purpose.

[0031] [Carbon-coated ceramic continuous fibers] The carbon-coated ceramic continuous fiber obtained by the production method of this embodiment has a carbon layer at least on the surface of the ceramic continuous fiber, and it is preferable that the carbon layer covers the surface of the ceramic continuous fiber. The carbon constituting the carbon layer may be one or more selected from the group consisting of graphite, amorphous carbon, and irregular carbon. In addition, the carbon may be a decomposition product of a carbon precursor containing oxygen, hydrogen, nitrogen, and carbon.

[0032] The thickness of the carbon layer may be any thickness suitable for the purpose or use, and may be, for example, 0.1 nm or more, 1 nm or more, or 10 nm or more, and 1000 nm or less, 300 nm or less, or 50 nm or less. For example, in the case of a ceramic continuous fiber used as a reinforcing material for a CMC, the carbon layer is preferably thin, and the thickness of the carbon layer may be 0.1 nm or more and 20 nm or less, 0.1 nm or more and 15 nm or less, or 0.1 nm or more and 10 nm or less.

[0033] In this embodiment, the thickness of the carbon layer may be calculated from the following formula.

[0034]

number

[0035] In the above formula, D f is the diameter of the ceramic continuous fiber [cm], ρ f is the density of the ceramic continuous fiber [g / cm 3 ], ρ C is the density of carbon [2.26g / cm 3 ] and △W is the value [mass %] calculated from the following formula:

[0036] △W = {(W2-W1) / W1}÷100 In the above equation, ΔW is the change in mass due to sintering [g], W1 is the mass of the ceramic continuous fiber before sintering [g], and W2 is the mass of the ceramic continuous fiber after sintering [g].

[0037] The firing may be performed using a general firing furnace (for example, FP410, manufactured by Yamato Scientific Co., Ltd.) under the following conditions. Firing atmosphere: Air Firing temperature: 800℃ Baking time: 1 hour Heating rate: 100℃ / h

[0038] [CMC manufacturing method] The carbon layer ceramic continuous fiber (hereinafter also referred to as "this continuous fiber") obtained by the manufacturing method of this embodiment can be used for known applications of ceramic continuous fibers, but is preferably used as a reinforcing material for ceramic matrix composite materials. A CMC can be obtained by a manufacturing method of CMC using this continuous fiber. When using this continuous fiber as a reinforcing material for CMC, a general CMC manufacturing method can be used, for example, a CMC manufacturing method having a mixing step of mixing a slurry containing a ceramic matrix precursor with this continuous fiber to obtain a mixture, a molding step of solidifying the mixture to obtain a molded body, and a firing step of firing the molded body.

[0039] In the mixing step, a slurry containing a precursor of the ceramic matrix (hereinafter also referred to as "raw material slurry") is mixed with the continuous fibers to obtain a mixture. The raw material slurry may contain a precursor of the ceramic matrix. The precursor of the ceramic matrix is ​​preferably a powder of an oxide ceramic, or at least one of alumina and mullite, or further preferably alumina powder.

[0040] The raw material slurry may contain an additive in addition to the ceramic matrix precursor. The additive is preferably a powder of an oxide ceramic different from the ceramic matrix precursor, such as at least one of silica and zirconia.

[0041] The continuous fibers to be subjected to the mixing step are preferably in a state in which a plurality of cloths, preferably 2 to 5 sheets, made of the continuous fibers are laminated.

[0042] The mixing step may be performed by any method that allows the ceramic matrix precursor to be evenly impregnated into the continuous fiber, and it is preferable to immerse the continuous fiber in the raw material slurry. The immersion conditions include the following: Immersion temperature: 100°C or higher or 110°C or higher, and 150℃ or less or 130℃ or less

[0043] The immersion time may be appropriately adjusted depending on the thickness of the continuous fiber, and may be, for example, from 2 hours to 10 hours, or from 3 hours to 9 hours.

[0044] In the molding step, the mixture is solidified to obtain a molded body. The molding method may be any method that allows the mixture to have a fixed shape, and may be one or more methods selected from the group consisting of heat treatment, freezing treatment, and additive treatment, with heat treatment being preferred.

[0045] Preferable conditions for the heat treatment include the following conditions. Heat treatment temperature: 50°C or higher, 60°C or higher, or 80°C or higher, and 160℃ or less or 140℃ or less Number of heat treatments: 1 to 5 times

[0046] The heat treatment time can be adjusted as desired depending on the amount of the mixture to be treated and the heat treatment temperature, and may be, for example, from 1 hour to 10 hours, or from 2 hours to 8 hours.

[0047] In order to improve operability, the method for producing a CMC according to the present embodiment may include a step of calcining the molded body to obtain a calcined body prior to the calcination step (hereinafter, also referred to as a "calcination step"). In this case, the calcined body may be subjected to the calcination step instead of the molded body.

[0048] In the calcination step, the compact is calcined to obtain a calcined body. The calcination conditions may be any conditions that allow necking between the particles of the matrix source to proceed, and examples of the calcination conditions include the following: Calcination atmosphere: oxidizing atmosphere or inert atmosphere, preferably air atmosphere Calcination temperature: 800°C or higher or 850°C or higher, and Less than 1000℃ or 900℃ or less

[0049] The calcination time may be arbitrarily changed depending on the size of the molded body and the characteristics of the calcination furnace used, and may be, for example, from 30 minutes to 120 hours.

[0050] In the firing step, the compact (or calcined body) is fired. This produces a CMC having the present continuous fibers. The firing may be performed under any condition that allows the sintering of the ceramic matrix to proceed, and examples of firing conditions include the following: Firing atmosphere: oxidizing atmosphere or inert atmosphere, preferably air atmosphere Firing temperature: 1000°C or higher, 1100°C or higher, or 1200°C or higher, and 1500℃ or less, 1450℃ or less, or 1400℃ or less Number of firings: 1 to 5

[0051] The firing time may be changed as desired depending on the size of the compact (or calcined compact) and the characteristics of the firing furnace used, and may be, for example, from 30 minutes to 120 hours. When firing is performed multiple times, the firing atmosphere and firing temperature may be set to any desired conditions.

[0052] The firing method is preferably a method in which the fired object (such as a compact or a calcined body) is heated without applying an external force during firing, that is, so-called "normal pressure firing." EXAMPLES

[0053] The present disclosure will be described in detail below with reference to examples. However, the present disclosure is not limited to these examples.

[0054] (Carbon layer thickness) The thickness of the carbon layer was determined by the following method: A firing furnace (FP410, manufactured by Yamato Scientific Co., Ltd.) was used to fire the carbon-coated ceramic continuous fiber under the following conditions. Firing atmosphere: Air Firing temperature: 800℃ Baking time: 1 hour Heating rate: 100℃ / h

[0055] The film thickness was calculated from the mass of the ceramic continuous fiber before and after firing using the following formula.

[0056]

number

[0057] In the above formula, D f is the diameter of the ceramic continuous fiber [cm], ρ f is the density of the ceramic continuous fiber [g / cm 3 ], ρ C is the density of carbon [2.26g / cm 3 ] and △W is the value [mass %] calculated from the following formula:

[0058] △W = {(W2-W1) / W1}÷100 In the above equation, ΔW is the change in mass due to sintering [g], W1 is the mass of the ceramic continuous fiber before sintering [g], and W2 is the mass of the ceramic continuous fiber after sintering [g].

[0059] (fiber volume ratio) The fiber volume fraction was calculated from the following formula.

[0060] Fiber volume fraction [volume%] = (V f / V CMC ) x 100 In the above formula, V f is the volume of the ceramic continuous fiber [cm 3 ] and V CMC is the volume of the CMC [cm 3 ]. Also, V f and V CMC is the value calculated from the following formula: V f = m / ρ f V CMC = A × B × t In the above formula, m is the mass of the ceramic continuous fiber [g] and ρ f is the density of the ceramic continuous fiber [g / cm 3 ], and A, B and t are the length [cm], width [cm] and thickness [cm] of the CMC, respectively, values ​​determined by dimensional measurements using a vernier caliper or a micrometer.

[0061] (Tensile strength) Tensile strength was measured using a strength tester (apparatus name: AG-XPlus, manufactured by Shimadzu Corporation) and a tensile test jig according to a method in accordance with JIS R 1656. Measurements were performed twice, and the average value was calculated. The CMC sample was processed to a width of 10±1 mm, length of 110±10 mm, and thickness of 2±1 mm, and aluminum tabs were attached to both ends to make a tensile test piece. The width and thickness of the tensile test piece were measured using a micrometer, and the length of the test piece was measured using a vernier caliper. The loading speed was 0.5 mm / min.

[0062] [Preparation of continuous ceramic fibers with carbon layers] Examples A1 to A5 Commercially available alumina and mullite continuous fiber cloth (product name: Nextel-720, manufactured by 3M Co.; ceramic continuous fiber with α-alumina and mullite crystal structures, Al2O3 content of 85 mass% and SiO2 content of 15 mass%, fiber diameter: 13 μm, fiber density: 3.4 g / cm3) 3 ) was heat-treated in air at 800°C for 1 hour to remove the sizing material, and the result was a desizing treatment.

[0063] Each polymer solution was prepared by dissolving polyvinyl acetate (molecular weight: 100,000) in methanol heated to 60° C. in the proportions shown in Table 1 below, and then allowing the solution to cool naturally to room temperature.

[0064] The desized continuous fiber cloth was immersed in each polymer solution at room temperature for 24 hours.

[0065] The impregnated continuous fiber cloth was washed with 1,000 g of ethanol solution, dried in air at 60°C for 2 hours, and then heat-treated in a nitrogen atmosphere at 500°C for 10 hours to obtain a carbon-coated ceramic continuous fiber cloth for each example. The results are shown in the table below.

[0066] [Table 1]

[0067] From Table 1, it was confirmed that the coating layer obtained becomes thicker by increasing the polymer concentration of the polymer solution. From this, it was confirmed that the method of the example makes it easy to control the thickness of the coating layer without repeating the immersion operation.

[0068] [Preparation of CMC] Examples B1 to B5 The carbon-coated ceramic continuous fiber cloth obtained in Examples A1 to A5 was used to prepare CMCs. That is, 91 g of α-alumina powder (average particle size: 0.15 μm), 0.94 g of spherical silica powder (average particle size: 0.24 μm), 1.9 g of yttrium-stabilized zirconia powder (average particle size: 0.04 μm) with an yttrium content of 3 mol%, and 31 g of dilute nitric acid water (pH = 2) were mixed to obtain a raw material slurry. The mixing was performed by ball milling for 24 hours using alumina balls with a diameter of 10 mm as a grinding medium. The obtained raw material slurry had a solid content concentration of 75 mass%.

[0069] Five sheets of ceramic continuous fiber cloth with carbon coating layer were laminated and immersed in the mixed slurry, and then heat-treated twice at 120±10°C for 6±2 hours to obtain a molded body with a width of 110 mm, length of 130 mm, and thickness of 2 mm. The compact was heat-treated in air at 900°C for 2 hours to obtain a calcined body, which was then heat-treated in air at 1100°C and cooled to room temperature. The temperature was then increased again and heat-treated in air at 1200°C to obtain CMCs of Examples B1 to B10.

[0070] The results, as well as the strength retention rate before and after heat treatment (thermal exposure treatment) in an air atmosphere at 1200°C for 1000 hours, are shown in the table below. In the table below, the comparative example is a CMC obtained in the same manner as in Examples B1 to B5, except that desized mullite fibers were used as the continuous fibers.

[0071] [Table 2]

[0072] From the above table, it can be confirmed that the strength retention rate of the CMC is improved by having a coating layer.

[0073] [Preparation of continuous ceramic fibers with carbon coating layer] Examples A6 to A10 A continuous ceramic fiber with a carbon coating layer was obtained in the same manner as in Examples A1 to A5, except that a resol type phenolic resin with a non-volatile content of 71% (containing 29% water) was used instead of polyvinyl acetate (molecular weight: 100,000). The results are shown in the table below.

[0074] [Table 3]

[0075] [Preparation of CMC] Examples B6 to B10 The CMC of each Example was obtained in the same manner as in Examples B1 to B10, except that the ceramic continuous fiber cloth with the carbon coating layer obtained in Examples A6 to A10 was used.

[0076] The results are shown in the table below.

[0077] [Table 4]

Claims

1. A method for producing a carbon-coated ceramic continuous fiber, comprising: an impregnation step of impregnating a ceramic continuous fiber with a solution containing a carbon precursor; a washing step of washing the ceramic continuous fiber containing the carbon precursor; and a heat treatment step of heat treating the washed precursor continuous fiber in an inert atmosphere or a vacuum atmosphere.

2. The method according to claim 1 , wherein the cleaning step uses a cleaning solution.

3. The method according to claim 2, wherein the cleaning liquid is at least one selected from the group consisting of water, methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, butyl alcohol, isobutyl alcohol, acetone, methyl ethyl ketone, methyl isobutyl ketone, diisobutyl ketone, cyclohexanone, diacetone alcohol, benzene, toluene, xylene, ethyl acetate, methyl acetate, butyl acetate, methoxybutyl acetate, isobutyl acetate, normal hexane, heptane, cyclohexane, methylcyclohexane, ethylene glycol, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, N,N-dimethylformamide, tetrahydrofuran, N-methyl-2-pyrrolidone, and 1,4-dioxane.

4. The method according to claim 1 or 2, wherein the ceramic continuous fiber is a ceramic continuous fiber cloth.

5. 3. The method according to claim 1, wherein the ceramic continuous fibers are continuous fibers of one or more materials selected from the group consisting of silicon carbide, alumina, and mullite.

6. 3. The method according to claim 1, wherein the carbon precursor is at least one selected from the group consisting of polyvinyl chloride, polyvinyl alcohol, polyvinyl acetate, polycarbonate, polyvinyl butyral, polystyrene, acrylic resin, methacrylic resin, polyphenylene oxide, thermoplastic polyurethane, polyethylene, polypropylene, polyamide, polyacetal, polyphenylene sulfide, vinylidene chloride resin, polyethylene terephthalate, phenolic resin, urea resin, melamine resin, unsaturated polyester resin, diallyl phthalate resin, epoxy resin, polyimide, polyamino bismaleimide, and thermosetting polyurethane.

7. A method for producing a ceramic matrix composite material, which uses the carbon-coated ceramic continuous fiber obtained by the method according to claim 1 or 2.

Citation Information

Patent Citations

  • JP2012-536852A